Pengaruh Utilitarian Shopping Value, Hedonic Shopping Value, dan Distribution Channels terhadap Intent to Repurchase pada Konsumen Lady Fame Shop di Bandar Lampung - Lestari, Resti (Jurnal Kompetitif Bisnis, 2022)
ABSTRACK : This study aims to determine how much influence the variables of utilitarian shopping value, hedonic shopping value, and distribution channels have on the intent to repurchase of lady fame shop consumers in Bandar Lampung. The size of the population is taken from the Lady Fame Shop Instagram followers as of June 2021, amounting to 1,000,000 followers. Sampling using simple random sampling technique to get 100 respondents. Collecting data in the field using a questionnaire distributed via google form. Data analysis in this study used simple linear analysis and multiple linear analysis with SPSS. Based on the results of research and data analysis, it is shown that simultaneously the utilitarian shopping value (X1), hedonic shopping value (X2), and distribution channels (X3) variables have a positive and significant effect on consumer intent to repurchase at the Lady Fame shop by 61.6%, or with In other words, 38.4% of the intent to repurchase variables were influenced by other factors not examined in this study.